Original paper BNP concentration in patients with mitral stenosis. Dependence on selected morphological parameters - Irzmański, Robert; Banach, Maciej; Piechota, Mariusz; Barylski, Marcin; Serwa-Stępień, Ewa; Cierniewski, Czesław; Jegier, Bogdan; Kowalski, Jan; Pawlicki, Lucjan (Archives of Medical Science, 2006)
Introduction: The study was carried out to estimate BNP concentration in patients with mitral stenosis and to check dependence of this concentration on the selected morphological parameters. Material and methods: Investigations were performed in two groups. Group I comprised 24 patients (mean age 55 years) with mitral stenosis without other coexistent heart diseases. Group II included 18 subjects (mean age 53 years) with excluded circulatory system diseases. The following parameters were examined: mean mitral valve area (MVA), mean mitral valve gradient (MVG) and maximal pulmonary arterial pressure (MPAP). Dimensions of cardiac cavities were also compared: left ventricular end-diastolic diameter (LVEDd), left atrial diameter (LAd), right ventricular diameter (RVd), and thickness of posterior wall diameter (PWd) and interventricular septum diameter (IVSd) were estimated. BNP was determined in blood samples by the radioimmunological method. Results: Mean BNP concentration in group I was elevated as compared to group II. In subgroups: Ia (with atrial fibrillation) and Id (with right ventricular hypertrophy), BNP concentration was also significantly elevated as compared to group II. Mean BNP concentration in group I correlated with MVA (r=-0.500) MVG (r=0.701), MPAP=(r=0.898) and with Lad (r=0.630) and RVd (r=0.870). Conclusions: The results of the study allow to state that BNP can be a useful, biochemical indicator of progression of morphological lesions accompanying mitral stenosis.